The Philosophy of Contract between Theory and Practice - Hamad, Hamad Kareem (Pakistan Journal of Humanities and Social Sciences, 2024)
This study provides a means of understanding Iraqi contract law's effectiveness. The foundation of the contract law mostly dealt with via the verbal interaction (deals and offers) between two different groups of individual (vendors and consumers) with tangible items or their actions. This study will consider the current contracts law used in the state of Iraq by employing models and theories of theory and practice contract law. Their confidence in successful agreement comes from authentications and legitimacy approaches. Additionally, it addresses issues pertaining to contract law in this jurisdiction and will be recognized by the efficacy of contract law in Iraqi nation determine whether Contract Law is useful to the Iraqi nation" is the stated study goal.